2020
DOI: 10.1111/ajco.13447
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes for patients with metastatic castrate‐resistant prostate cancer following docetaxel for hormone‐sensitive disease

Abstract: Aim Optimal treatment for newly diagnosed metastatic hormone‐sensitive prostate cancer (mHSPC) has evolved, with many patients deriving benefit from the addition of docetaxel to androgen deprivation therapy (D‐ADT). This study sought to define the therapy used and associated activity following D‐ADT. Methods Retrospective analysis of patients with mHSPC treated with one or more cycles of D‐ADT who were identified from a prospectively maintained multisite prostate cancer database of patients treated in a commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Docetaxel is also a member of the taxane class of anticancer drugs. Docetaxel alone or docetaxel-based regimens are employed in standard chemotherapy for various types of cancers [54,55]. A study showed that prolonged exposure to docetaxel and 5-fluorouracil (5-FU) in colon cancer cells (HT29 and LOVO cell lines) under hyperglycemia led to decreased anticancer effects of these drugs, and suppression of mROS production [32].…”
Section: Taxanementioning
confidence: 99%
“…Docetaxel is also a member of the taxane class of anticancer drugs. Docetaxel alone or docetaxel-based regimens are employed in standard chemotherapy for various types of cancers [54,55]. A study showed that prolonged exposure to docetaxel and 5-fluorouracil (5-FU) in colon cancer cells (HT29 and LOVO cell lines) under hyperglycemia led to decreased anticancer effects of these drugs, and suppression of mROS production [32].…”
Section: Taxanementioning
confidence: 99%
“…It is one of the most common cancers of the male genitourinary system worldwide and has a high incidence among male malignant tumors [1][2][3]. In patients with localized prostate cancer (LPCa), radical prostatectomy, radiotherapy and hormone deprivation therapy can markedly beneficial effects, prolonging the survival time of patients [4][5][6][7][8][9][10]. However, due to the lack of obvious symptoms and specific biomarkers in the early stage of PCa metastasis, the diagnosis and treatment of metastatic prostate cancer (MPCa) is commonly delayed.…”
Section: Introductionmentioning
confidence: 99%